Coleção de bustos-relicários da antiga Igreja do Colégio de Jesus de São Salvador da Bahia: preservação de 30 esculturas do Século XVII - Joao Carlos Silveira Dannemann (2003)
Study and restoration of the 30-sculpture collection (bust-reliquaries) from the 17TH century, named Virgin Saints Martyrs and Saints Martyrs, originally owned by the old church of Jesus' School in Salvador, Bahia, Brazil. The collection constructive technology, ornamentation and iconography analysis allowed the internal sub-groups identification, the systematization of the diagnosis of the Conservation State and the criteria establishment for the intervention. Classified the units by constructive technology and similar groups, it was feasible to identify some of the possible represented iconography, as well as select the most adequate materials and procedures to revert the conservation problems. Simultaneously, a research developed to achieve the historical context of the collection and a social-character didactic activity occurred on UFBA Sacra Art Museum Conservation and Restoration Workshop, the intervention place, training and qualifying young as Restoration Assistant.